Thrombin induces epithelial-mesenchymal transition via PAR-1, PKC, and ERK1/2 pathways in A549 cells. (1st October 2013) - Song, Jeong Sup; Kang, Chun Mi; Park, Chan Kwon; Yoon, Hyung Kyu
ABSTRACT Thrombin activates protease-activated receptor (PAR)-1 and induces a myofibroblast phenotype in normal lung fibroblasts. The origins of myofibroblasts are resident fibroblasts, fibrocytes, and epithelial-mesenchymal transition (EMT). We investigated the effects of thrombin, an important mediator of interstitial lung fibrosis, on EMT in A549 human alveolar epithelial cells. We show that thrombin induced EMT and collagen I secretion through the activation of PAR-1, and PKC and ERK1/2 phosphorylation in A549 cells. These effects were largely prevented by a specific PAR-1 antagonist, short interfering RNA (siRNA) directed against PAR-1, or specific PKCα/β, δ, and ε inhibitors. These data indicated that interaction with thrombin and alveolar epithelial cells might directly contribute to the pathogenesis of pulmonary fibrosis through EMT. Targeting PAR-1 on the pulmonary epithelium or specific inhibitors to PKCα/β, δ, and ε might stop the fibrotic processes in human idiopathic pulmonary fibrosis by preventing thrombin-induced EMT.